Thermal energy use for dehumidification of a tomato greenhouse by natural ventilation and a system with an air-to-air heat exchanger - Maslak, Katarzyna; Nimmermark, Sven (Agricultural and Food Science, 2017)
<span style="color: black; line-height: 110%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The aim of the study was to estimate the amount of thermal energy used for dehumidification of a naturally ventilated tomato greenhouse and to estimate how mechanical ventilation with the use of a heat exchanger recovering heat from the exhaust to the supply air may decrease the energy use. Measured use of thermal energy in a naturally ventilated tomato greenhouse was compared to modelled values using Powersim® software. By the help of the model an estimation of the amount of energy used for dehumidification was made for the months April – September. A non-hygroscopic rotary air-to-air heat exchanger was studied, and its temperature and moisture efficiencies were measured. Modelling for leaf area index (LAI) 3.5 and 4.0 m2 m-2 indicated that 23 and 29% of the total thermal energy was used for moisture removal respectively. Modelling for the heat exchanger indicated thermal energy savings of 15 and 17% for the same LAI respectively.